Student Evaluations of Teaching: Understanding Limitations and Advocating for a Gold Standard for Measuring Teaching Effectiveness - Judith Marychurch; Kelley Burton; Michael Nancarrow; Julian Laurens (Legal Education Review)
The arbitrator’s decision in Ryerson University v Ryerson Faculty Association [2018] CanLII 58446 (ON LA) rejected use of Student Evaluations of Teaching (SETs) for academic confirmation and promotion purposes. SETs provide largely quantitative data in response to pre-determined institutional, generic questions using a Likert scale applicable to all teaching modes. SETs may be efficient, but commonly low response rates mean the data is often statistically invalid. Studies of SETs suggest gender, age, race, and other biases are widespread, and they discourage teaching innovation because academics fear student backlash in SET scores. Consequently, SETs are of little value to academics for their professional development, confirmation or promotion, or as evidence for teaching grant or awards processes. The continuing impact of the COVID-19 pandemic on traditional models of teaching has forced many changes in teaching, learning and pedagogy, often with a temporary suspension of SETs to allow teachers to innovate without negative impact on professional development measures. This presents a unique opportunity for us to revisit how the effectiveness of teaching and learning is measured. Academic teaching staff still need evidence of teaching effectiveness, as do sessional staff looking for continued employment and/or a career in academia. This paper discusses the strengths and weaknesses of SETs; seeks to equip law academics to advocate for other measures of teaching effectiveness that better reflect their contribution to student learning; and to pave the way for law discipline and institutional level changes that support a gold standard in measuring teaching effectiveness beyond reliance on SETs, for the benefit of teachers in law and other disciplines.